Corporate Classicism and the Metaphysical Style: Affects, Effects, and Contexts of Two Recent Trends in Screen Scoring. Issue 2 (December 2015) - Reyland, Nicholas
Abstract : Situating the aesthetic practices of recent narrative film scoring within debates on 'intensified' or 'post-continuity' style, as well as accounts of reception in terms of post-cinematic affect or distributed subjectivity, this paper identifies two significant stylistic tendencies in film scoring: 'corporate classicism' and 'the metaphysical style'. Examples are drawn from film and a wider range of musical media, with an analytical focus on representative cues from Hans Zimmer and James Newton Howard's score to The Dark Knight (2008) and Thomas Newman's score to American Beauty (1999). The two styles of screen music scoring, orchestration, production, and post-production beg reminders not only of the problematic 'utopian' call of classical Hollywood film scoring (Flinn 1992), but also suggest that the powerful affective work performed by these scores raises the question of 'unheard melodies' (Gorbman 1987) anew.